2019
DOI: 10.1002/ijc.32516
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair and cancer in colon and rectum: Novel players in genetic susceptibility

Abstract: Interindividual differences in DNA repair systems may play a role in modulating the individual risk of developing colorectal cancer. To better ascertain the role of DNA repair gene polymorphisms on colon and rectal cancer risk individually, we evaluated 15,419 single nucleotide polymorphisms (SNPs) within 185 DNA repair genes using GWAS data from the Colon Cancer Family Registry (CCFR) and the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO), which included 8,178 colon cancer, 2,936 rectum can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The activation of PI3K/AKT signaling has been shown to promote EMT ( Liu et al, 2018 ). “Wnt/beta-catenin signaling”, “MYC target v1”, and “DNA repair” are closely related to tumorigenesis and the development of HCC ( Dolezal et al, 2017 ; Dimri and Satyanarayana, 2020 ; Pardini et al, 2020 ). Taken together, the findings clearly suggest that these genes are closely associated with the mechanisms underlying HCC cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of PI3K/AKT signaling has been shown to promote EMT ( Liu et al, 2018 ). “Wnt/beta-catenin signaling”, “MYC target v1”, and “DNA repair” are closely related to tumorigenesis and the development of HCC ( Dolezal et al, 2017 ; Dimri and Satyanarayana, 2020 ; Pardini et al, 2020 ). Taken together, the findings clearly suggest that these genes are closely associated with the mechanisms underlying HCC cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Several association studies addressed the role of low penetrance BER gene variants in sporadic CRC with often controversial results. The recent whole genome association studies failed to identify these variants in large CRC patient cohorts [5,145]. Despite it was shown that hOGG1 326Cys SNP significantly affected BER DRC, the overall effect is rather minor, and these gene variants may rather find their relevance in interactions [146,147].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis further strengthened the above evidence for rs1800734 as an event in a specific CRC subtype ( p = 3.43 × 10 −12 ) [ 40 ]. Finally, a recent study based on genome-wide association studies (GWAS) data by Pardini et al comprising over 27,000 individuals showed rs1800734 to be significantly associated with the risk of colon cancer (OR = 1.13, 95% CI = 1.07–1.18, p = 3.48 × 10 −6 ) [ 55 ]. When looking at tumour site, rs1800734 was mainly associated with proximal colon tumours (OR = 1.13, 95% CI = 1.07–1.18).…”
Section: Results On Mmr Gene Variantsmentioning
confidence: 99%